Efficacy of different polypill combinations for primary and secondary cardiovascular disease prevention: a systematic review and meta-analysis - Yazgi, Habib; Mattikalli, Shivani; Fang, Brian; Heselton, Hannah; Ssentongo, Paddy; Farbaniec, Michael (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease is the leading cause of mortality and morbidity worldwide, and polypills have established efficacy in preventing poor outcomes. However, evidence on the optimal polypill combination is lacking. The objective of the study is to estimate the optimal polypill combination that maximizes cardiovascular outcomes.MethodsMEDLINE/PubMed, Scopus, and Cochrane Database of Systematic Reviews databases were searched from January 1, 1960, to March 30, 2025. Studies that provided data on the association between polypill and cardiovascular outcomes were included. We estimated the effect of various polypill combinations by random-effects meta-analyses using the generic inverse variance method. Subgroup and meta-regression analyses were conducted to explore potential effect modification in the association between polypill combinations and cardiovascular outcomes.ResultsThirty studies comprising 35,833 individuals met the inclusion criteria from 6 continents. The estimated pooled effects of polypill use on major adverse cardiovascular events (MACE), cardiovascular death, and all-cause mortality were RR 0.78 (95% CI, 0.63–0.97), 0.75 (95% CI, 0.63–0.89), 0.88 (95% CI, 0.79–0.98), respectively. The pooled relative risk of MACE outcome was 21% lower in combination of 4 or more pills [0.79 (95% CI, 0.55–1.15), n = 6 studies] vs. to 22% and 3 or less combination of medication classes (RR: 0.78 95% CI: 0.70–0.86), n = 4 studies). Polypill combinations containing moderate or high-intensity statins were associated with lower risk of MACE outcomes RR 0.79 95% CI: 0.70–0.97), n = 2 studies compared to combinations with low-intensity statins RR 0.78 95% CI: 0.59–1.03, n = 8). All polypills for MACE outcomes contained RAAS inhibitors. Calcium channel blockers, RAAS inhibitors and diuretics-containing polypills were associated with the highest reduction in blood pressure. Certainty of evidence for MACE ranged from low to high, with most trials rated as moderate to high.ConclusionsIn this meta-analysis, polypills with 3 cardiovascular classes that contain a high-intensity statins, aspirin and RAAS inhibitors appeared to have greater reduction in MACE outcomes. The presence of a diuretic and a calcium channel blocker in the polypill was associated with greater reductions in systolic and diastolic blood pressure.